South Africa–China Relations
XXIV, 298 p. 19 illus., 17 illus. in color.
Keywords: This comprehensive analysis of South Africa-China relations represents the research of some of the best minds working on China-Africa issues. It reflects the thoughtful perspectives of scholars from Africa, China and Western countries. – David Shinn, George Washington University, Washington DC, USA This book is a refreshingly blunt, thought provoking, and provides a thoroughly informed discussion of China –South Africa relations. Unlike several China Africa books that tend to demonstrate a bias towards either Chinese or Western thinking, this book unapologetically dispels any myths or narratives surrounding China-South Africa political and economic relations. The various sections in the book shed excellent light on the political influences shaping economic diplomacy, particularly given the complex global, regional and local economics regarding both countries. This is also one of the very few books that scientifically unpacks identity, and the impact of economic transformation on South Africa’s local Chinese community. The book sections serve as an invaluable resource for policy makers, civil societies, and academics interested in understanding South Africa-China bilateral ties. – Dr Funeka Yazini April, Coordinator, BRICS Research Center, Human Sciences Research Council, Pretoria, South Africa With the pace of trade and investment picking up, coupled with closer international cooperation with Beijing through the G20, FOCAC and BRICS grouping, South Africa-China ties are assuming a significant position in continental and even global affairs. At the same time, it is a relationship of paradoxes, breaking with many of the assumptions that underpin contemporary analyses of ‘China-Africa’ ties. This edited volume examines the South Africa-China relationship through a survey of its diplomatic partnership, economic ties, and broader community relations. These important aspects that are often conflated as a single relationship, yet what is important to explore are how these components reflect different China-South Africa relationship(s), and how they intersect. Chris Alden is Professor in International Relations at the LSE and Director of LSE-IDEAS. He is a Senior Research Associate with the South African Institute of International Affairs and a Research Associate with the Department of Political Sciences, University of Pretoria. Yu-Shan Wu is Research Associate with the Africa-China Reporting Project (ACRP) at the University of the Witwatersrand, South Africa.